Concepções sobre a questão indígena: província de São Paulo, 1822-1834 - Azevedo, Larissa Biato de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this work is to understand how the indigenous issue was politically conceived during the first two decades of the nineteenth century. In this period of important discussions about the formation of the Brazilian national state, the contemporaries sought to establish guidelines for the treatment of indigenous peoples of the Empire of Brazil, which concerned the definition of means to civilization of these individuals. We explore this issue through parliamentary discussions, laws and projects, highlighting three proposals from characters of the province of São Paulo, presented between 1822 and 1823, and the positions of members of the Presidential Council and the General Council of the same province, organisms that were active from 1824 to 1834. Although an indigenous law has not been set at this time, the conceptions of indigenous issue showed the pursuit of new directions to the civilization of Indians on the political pact that was in formulation in the Empire

O objetivo deste trabalho é compreender como a questão indígena foi politicamente concebida durante as duas primeiras décadas do século XIX. Neste período de discussões caras à formação do estado nacional brasileiro, os contemporâneos procuraram estabelecer diretrizes para o trato das populações indígenas do Império do Brasil, o que dizia respeito à definição de meios para a civilização desses indivíduos. Exploramos essa temática por intermédio de discussões parlamentares, de leis e de projetos, destacando três propostas oriundas de personagens da província de São Paulo, apresentadas entre 1822 e 1823, e os posicionamentos dos membros do Conselho de Presidência e do Conselho Geral dessa mesma província, órgãos que estiveram em atividade de 1824 a 1834. Embora uma legislação indigenista não tenha sido definida nessa época, as concepções sobre a questão indígena mostraram a busca por novos sentidos para a civilização dos índios em meio ao pacto político que então se formulava no Império
Keywords: História; Política social; Indios - Trato - São Paulo (Estado); Indios - Questões sociais e morais; Brasil - Historia - I Reinado - 1822-1831